Interfacial challenges towards stable Li metal anode. (January 2021) - Luo, Zheng; Qiu, Xuejing; Liu, Cheng; Li, Shuo; Wang, Chiwei; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Rechargeable Li metal batteries once had a glory moment in 1980s, but its development was sooner suspended for safety concerns from dendrite formation. After falling into oblivion for several decades, Li metal anode is reviving in recent years with the ever-growing demands for high energy devices. Despite great progresses have been achieved, current Li metal anode still lacks of efficiency and safety. Essentially, Li deposition is a process involving the transport and reduction of Li ions on different interfaces. Therefore, deeply understanding the interfacial chemistry and kinetics of metallic Li is of vital significance towards practical Li metal anodes. In this review, key interfacial challenges faced in Li metal anode and their initiation mechanisms are comprehensively summarized. Furthermore, the prospective developments and alternative approaches towards these challenges are presented to better regulate the interfaces and improve the performance of Li metal anode. Graphical Abstract: Since Li metal deposition is a process of mass transfer and reduction reaction, the interfaces largely determine the deposition behavior and the electrochemical performance of Li anode.In this review, key interfacial challenges faced in Li metal anode and their initiation mechanisms are summarized to provide the directional guidance for elaborately designing stable and efficient interfaces towards high-performance Li metal batteries. ga1 Highlights: The interfacial challenges of Li metal anodes and their initiation mechanisms are comprehensively summarized. Interfacial strategies towards high performance Li metal anode are highlighted. An outlook on future research directions is given.